PEMBELAJARAN STATISTIKA DALAM PERSPEKTIF GENDER - Yuyun Yunarti (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2018)
Statistics is considered a boring subject for students, even though statistics are taught with the aim of preparing students to be able to use statistics in their daily lives. In studying statistics, there are still many students both men and women who view statistics as a boring subject. Based on this, the gender aspects of statistical learning are of concern to educators. Gender differences not only result in differences in abilities in statistical courses, but also in obtaining statistical knowledge. Many opinions say that women are not enough to successfully study statistics compared to men. In addition, women almost never have a thorough interest in theoretical questions like men. Women are more interested in practical things than theoretical ones. But on the other hand, not a few female students have success in statistical abilities.